Shifting foundations and metrics for golden‐cheeked warbler recovery - Jeff S. Hatfield; Floyd W. Weckerly; Adam Duarte (Wildlife Society Bulletin)
Abstract Using the golden‐cheeked warbler (Setophaga chrysoparia) as a case study, this paper discusses what lessons can be learned from the process of the emergency listing and subsequent development of the recovery plan. Are the metrics for recovery in the current warbler plan appropriate, including population size and distribution (recovery units), migration corridors, and wintering habitat? In other words, what happened, what can we learn, and what should happen (in general) in the future for development of such plans? We discuss the number of recovery units required for species persistence and estimate the number of male warblers in protected areas across the breeding range of the species, using newly published density estimates. We also discuss future monitoring strategies to estimate warbler population trends and dispersal rates. © 2012 The Wildlife Society.